PERCEPTIONS OF RELATIONSHIP VIOLENCE: A YOUTH PERSPECTIVE - Pretorius, Blanche; Terblanche, Susan; Tshiwula, Lullu (Social Work/Maatskaplike Werk, 2007)
Youths constitute a significant and growing sector of the population living in South Africa. Dickson-Tetteh and Ladha (2000:2) state that there are currently about 18 million people under the age of 20 years, who constitute 44% of the total population. McWhirter, McWhirter, McWhirter and McWhirter (2004:4) suggest that the well-being and stability of society depend on our ability to prepare well-adjusted and responsible young people to step forward to take up their roles as the older generation passes. In contemporary society the youth face a host of challenges that can impact either positively or negatively on their ability to negotiate the transition from childhood to adulthood. During adolescence youths complete crucial life-tasks and as such are especially vulnerable to the effects of violence as both perpetrators and victims.